Educação matemática no Ensino de Ciências: contribuições da teoria dos conjuntos na educação de jovens e adultos - uma proposta metodológica - Barros, Ana Maria dos Santos (2011)
Mathematical education in the Teaching of Sciences, is discussed with emphasis to the teaching of the Theory of the Conjuncts in the Second Segment of the Education of Youths and Adults (EJA). Para the progress of the Education, an emphasis is given to the historical and philosophical context with the considerations to the History of the Mathematics and Progresses in the Mathematical Education in Brazil. He/she comes a connection among: Logic, Scientific Methods and the Theory of the Conjuncts to be discussed in the Teaching of Sciences. He/she is considered in this research the Axiomatic method starting from the Aristotelian Logic with exemplificações of syllogisms to the preliminary study the Theory of the Conjuncts. Among the mathematicians, Singer was selected among the centuries XVIII to XIX, for considering their ideas in the creation of the Theory of the Conjuncts. He/she comes the definition of the Theory of the Conjuncts from the intuitive notion of groups to the teaching of Sciences for contributions in theories of the several areas of the knowledge. The Mathematical Education appears as Proposed Curricular the Education of Youths and Adults with observations to the qualitative and quantitative reasoning, the Theory of the Conjuncts is discussed in the results obtained after the application of a research instrument to the students of the Education of Youths and Adults in the night schedule in school of the city of Manaus. Some problems were diagnosed, such as: scientific methods, the mathematical language, the language of groups and the notions of Logic, besides the geometric interpretations, applications of the simbologia of the Mathematics, the historical contextualização and the applications of the theory to situation-problems. For not being considered by some authors of text books, the Theory of the Conjuncts has been causing interferences in the learning of Mathematics of the Education of Youths and Adults. The analysis of the application of the questionnaire the Education of Youths and Adults, it seeks the construction of a text book while Proposed Curricular and Methodological to the students of the First and Second Segment EJA. The analysis is mentioned of some text books with some descriptions along a pedagogic practice. He/she identified the scientific problems starting from the analysis, of the elaboration of the questionamentos in proposed subjects. Finally, some considerations the Education of Youths and Adults for the professionals of other areas of the knowledge that supply Mathematics for this Modality of Teaching. The Research is a Proposed Curricular and Methodological with educational purposes and merely didacticisms the Mathematical Education to be discussed with the Coordination of Youths and Adults (COEJA) so that other problems are diagnosed in the educators' formation in Mathematical Education